PENGARUH PENDIDIKAN GIZI TERHADAP PENGETAHUAN DAN PRAKTIK MEMBAWA BEKAL MENU SEIMBANG ANAK SEKOLAH DASAR - Adelwais Febriati Yurni; Tiurma Sinaga (Media Gizi Indonesia, 2017)
This study aims to analyze the effect of nutrition education on knowledge and practice of bringing a balanced meal box among school-aged children. The study design was quasy experimental study with one group pre and post-test. Subjects are 52 students of grade 5 at SDN Babakan Dramaga 04, Bogor District. Nutrition education was done twice for 2 weeks. Post-test 1 nutritional knowledge was done 1 week after intervention, and practice of bringing balance meal box was done 2 weeks after intervention. Post-test 2 and post-test 3 practice of bringing balance meal box was conducted every 2 weeks. Subject’s anthropometry was measure at the beginning and the end of the study. The results showed that knowledge of balanced nutrition increased after receive nutrition education. Subject show an improvement in the practice of bringing balance meal box after nutrition education intervention. This study recommend the school to continue asking the student to bring balance meal box, and monitored by sport teacher. Parents should support students by providing a balanced and nutritious food.